Cassava bread in Nigeria: the potential of 'orphan crop' innovation for building more resilient food systems. (2017) - Pereira, Laura M.
Achieving global food security sustainably is a great challenge in the 21st century. This paper proposes that orphan crop innovation has the potential to help address this need. Using the case study of cassava bread in Nigeria, it demonstrates the barriers to and mechanisms for developing innovation systems for orphan crops. It finds that the goal-oriented search for cassava bread was successful, but the wider systemic weakness that its invention was supposed to address required further interventions. Furthermore, when the benefits of a specific product do not accrue directly to the end-users, but are felt further up the supply chain, it is difficult to incentivise the private sector to invest in these types of innovation because there is no clear target market. This requires collaboration and trust between public and private sector actors, which is especially important due to ethical concerns in bridging formal technological innovation with traditional knowledge systems.